Brain metastasis: New opportunities to tackle therapeutic resistance. Issue 6 (2nd June 2014) - Seoane, Joan; De Mattos-Arruda, Leticia
Abstract : Brain metastasis is a devastating complication of cancer with unmet therapeutic needs. The incidence of brain metastasis has been rising in cancer patients and its response to treatment is limited due to the singular characteristics of brain metastasis (i.e., blood—brain‐barrier, immune system, stroma). Despite improvements in the treatment and control of extracranial disease, the outcomes of patients with brain metastasis remain dismal. The mechanisms that allow tumor cells to promulgate metastases to the brain remain poorly understood. Further work is required to identify the molecular alterations inherent to brain metastasis in order to identify novel therapeutic targets and explicate the mechanisms of resistance to systemic therapeutics. In this article, we review current knowledge of the unique characteristics of brain metastasis, implications in therapeutic resistance, and the possibility of developing biomarkers to rationally guide the use of targeted agents. Highlights: Brain metastasis is a devastating complication of cancer with unmet therapeutic needs. Brain metastasis exhibits unique biologic characteristics that interfere with systemic therapeutics. There is a need to identify the molecular mechanisms inherent to brain metastasis to improve their treatment. Biomarkers for molecular diagnosis are required for a better managing of the disease.